Peran vegetasi dalam meningkatkan kualitas aksesibilitas di ruang terbuka publik (studi kasus: Taman Vatulemo) - Permata, Nike Dyah; Prastiyo, Yulius Budi; Nabilah, Rizka; Sari, Pawitra (Agrokompleks, 2025)
Urban parks serve as areas that support social interaction and enhance the quality of life for the community. These parks feature vegetation that enhances their aesthetic and provides ecological benefits. Vegetation contributes to visitor comfort and improves park accessibility. However, suboptimal vegetation planning can hinger accessibility for certain groups, such as disabilities, elderly, and children. This study aims to analyze the role and impact of vegetation on accessibility in Vatulemo Park. The research begins with observations, spatial analysis using GIS to examine the distribution of vegetation and circulation patterns park. Additionally, a landscape design evaluation is conducted based on Universal Design principles and accessibility standards for green open spaces. The findings indicate that the distribution of vegetation in Vatulemo Park does not fully support accessibility. Shaded areas along circulation paths and jogging tracks are still insufficient, making the park less comfortable for visitors, especially between 10:00 AM and 4:00 PM WITA. Moreover, the lack of vegetation around seating areas and gathering spaces reduces the park's ecological function and user comfort. Therefore, recommendations for improving vegetation placement within the park are necessary to increase greenery along circulation paths and jogging tracks. The selection of plant species should also be adjusted to avoid obstructing visitor activities and comfort. Furthermore, chosen vegetation should not hinder accessibility, and user-friendly pathways should be provided for individuals with special needs. By implementing these strategies, Vatulemo Park is expected to become a more inclusive, comfortable, and ecologically sustainable public space for the residents of Palu City.